The effect of marketing mix on purchasing decisions - Muliyati Muliyati (Institute of Computer Science (IOCS), 2023)
The research objective is to determine the effect of marketing mix on purchasing decisions both partially and simultaneously. The sampling technique is accidental sampling, the respondents taken are consumers who have made repeated purchases, with a total of 150 respondents. Data analysis using multiple regression. The research results obtained, namely the R value of 0.489, proved to have a strong positive and significant influence between the marketing mix on purchasing decisions. The R Square value of 0.217 or 21.7% indicates that there is an influence of the independent variable on the dependent variable (purchase decision) of 21.7%. Simultaneously Fhitung> Ftabel (4.325> 2.33), so in this case the first hypothesis is accepted. The conclusion of the study shows that partially the price variable and the physical environment have a significant effect on the purchasing decision variable. Meanwhile, the product variable, promotion variable and service variable partially have no significant effect on the purchasing decision variable. The independent variable that has the most dominant effect on the dependent variable is price and the price variable has a dominant influence on the purchasing decision variable.